Constructing a New Weighted Maxwell Probability Distribution with Comparing of its two Parameters - A.L. Noora Ali Azeez (Iraqi Journal for Administrative Sciences, 2024)
This paper discuss the Maxwell distribution with scale parameter (θ), and how to expand this family to find weighted Maxwell p.d.f which is necessary for sampling from population of different sizes, so we apply some transformation on [f_T (t;θ)] to obtain [g_w (t)], then its C.D.F obtained. Also the formula for r^th moments about origin also derived to help in finding moment estimators of (β).